Politik Pangan Lokal "Setengah Hati" Indonesia Setelah Pandemi COVID-19 - Ramadhan, Rury; Armin, Armin; Saad, Muhammad (Palita: Journal of Social Religion Research, 2022)
The COVID-19 pandemic brings the threat of a global food crisis. Indonesia's food system is vulnerable because it only depends on one type of food, namely rice. Hopes about Indonesia's food security have returned to the potential for local food diversity, as well as moving from food security to food sovereignty. This study will focus on the process of developing local food in Indonesia which is considered a way out of the threat of a global food crisis due to the COVID-19 Pandemic. The purpose of this study is to find out a general description of the condition of local food in Indonesia so far. The method used in this research is desk research using a political-economic approach in the context of neoliberalism. The results of this study indicate that Indonesia is "half-heartedly" in developing local food as a result of its position between the dichotomy of food sovereignty versus global trade liberalization.